FORECAST OF CHANGE IN GROUND WATER LEVEL UNDER INFLUENCE OF HORIZONTAL SYSTEMATIC DRAINS: (on the example of the Ararat plain) (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
The article considers changes in groundwater level under the influence of horizontal systematic drainages. The filtration resistance method is used to calculate the dynamics of groundwater level increase in the middle of the drainage distances in irrigated lands under the conditions of unstable filtration. The calculation results show that in irrigated lands, the maximum increase in groundwater level in the middle of drainage distances is 1–1.16 m. Therefore, if the design parameters of the drainage are maintained, the increase in the level of groundwater during the vegetation season is within or below the mark of the drying depth.
Keywords: groundwater level; horizontal drainage system; filtration resistance; irrigated lands